AC/DC Convertible Pillar‐Type Triboelectric Nanogenerator with Output Current Amplified by the Design of the Moving Electrode. Issue 9 (21st January 2022) - Kim, Dongchang; Chung, Jihoon; Heo, Deokjae; Chung, Seh‐Hoon; Lee, Giuk; Hwang, Patrick T. J.; Kim, Min‐Kun; Jung, Heesoo; Jin, Youngho; Hong, Jinkee; Lee, Sangmin
Abstract: As a valuable tool for harvesting energy, triboelectric nanogenerators (TENGs) exhibit notable advantages over other energy‐harvesting methods in terms of their low weight, low cost and high‐power density. Despite their application potential in the domain of portable electronics, TENGs exhibit a limited maximum output owing to the high surface charge density during operation. Furthermore, TENGs inherently produce alternative current (AC); thus, an additional electrical circuit such as a rectifying circuit must be used as a portable power source. To overcome these problems, a triboelectric generation mechanism that can produce both AC and direct current outputs with amplified electrical current through the addition of a simple mechanical component is established. The proposed pillar‐type TENG (P‐TENG) can minimize the electrical loss during operation that occurs due to the contact between electrodes, allowing electrons to flow directly. Moreover, a miniaturized and portable variant of the P‐TENG is designed to harvest mechanical energy in daily‐life activities. Abstract : This paper reports an alternative current/direct current (AC/DC) convertible pillar‐type triboelectric nanogenerator that produces amplified current output and has an AC/DC selective mechanism by using high charge density air breakdown and movement of a ring electrode. It can be also designed as a miniature device to improve portability for everyday use.